Community Tourism Development by Identity Study and Publicizing: a Case Study of Bua-roi Temple, Bangsaothong District, Samutprakan Province - Lohapoontrakool, Jariyarwat (Academic and Research Journal of Liberal Arts (Online), 2022)
This research aimed to and publicize the community identity of Bua-roi Temple and its neighborhood for developing the area to be a tourist attraction. The distinguished identities were publicized to both local and general people through various channels. The area studied were the Bua-roi Temple and its surrounding communities. The sampling population was composed of 50 informants, including the abbot and monks of Bua-roi Temple, community sages and leaders; the Chief Executive and officials of Bang-sao-thong Subdistrict Administrative Organization; the director, teachers, and M5 students of Wat Bua-roi School; and 100 local people who usually attended the temple services. Data gathering tools inciuded interviewing, group discussion, brainstorming, analyzing meetings relating to the community, questionnaire, and note- taking. Research findings show that the community gained important information on four aspects of identities beneficial for promoting their tourist attraction, which were 1) historical identity; 2) aesthetic identity; 3) social values identity; and 4) environmental identity. For publicizing, videos and vinyl banners were created; also tourism personnel, including teachers and officials of Bang-sao-thong Subdistrict Administrative Organization were trained in English usage. Moreover, students were also trained on Thai language usage being youth tour-guides publicizing accurate identities of their tourist attraction.